Storybook berbasis augmented reality (AR) meningkatkan hasil belajar bahasa Inggris siswa - Pahlevi, Nihaya Rizki; Degeng, Made D. K.; Ulfa, Saida (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study focuses on the combination of digital media and students' literacy, utilizing an Augmented Reality (AR)-based storybook as a tool for English language subject. The aim of this research is to assess how the use of AR-based storybooks can influence and enhance students' learning outcomes in English language subject. Employing an experimental research design, two groups were exposed to different stimuli. The experimental group's test results showed a significant difference with a two-tailed significance value of 0.032, indicating an impact attributed to the utilization of AR-based storybooks. Additionally, the N-gain percentage results revealed a 60% improvement, categorizing the AR-based storybook as moderately effective in enhancing students' learning outcomes compared to conventional storybook media. The findings of this study indicate that the implementation of AR-based storybooks significantly and effectively enhances students' learning outcomes in English language subject.